THE IMPLEMENTATION OF DIGITALIZATION ON EMPLOYEE PERFORMANCE MODERATED BY EMPLOYEE ENGAGEMENT AT THE GENERAL BUREAU OF THE REGIONAL SECRETARIAT OF NORTH SUMATRA PROVINCE - Yusuf Toha Lubis; Yohny Anwar; Muhammad Isa Indrawan (RADJA PUBLIKA, 2025)
This study aims to explore the impact of digital transformation on employee performance, considering the level of employee engagement in the work environment of the General Bureau of the North Sumatra Provincial Secretariat (Setdaprovsu). The North Sumatra Provincial Government, specifically through the General Bureau of the Setdaprovsu, has begun implementing a digital technology-based work system to adapt to central government policies and developments in other regions that have already adopted digitalization. This implementation is expected to accelerate work processes, increase efficiency, and encourage increased employee productivity. However, some older employees experience difficulties adapting to the latest technological devices and systems. Low digital literacy among certain employees is a barrier to adapting to these changes. Therefore, it is important to explore the extent to which digitalization actually contributes to employee performance, and whether the level of employee work engagement can be a supporting factor in facing the challenges of digital adaptation. This study relies on quantitative methods by distributing an online questionnaire via the Google Form platform to 76 employees of the General Bureau of the Setdaprovsu as respondents. The data obtained is processed in numerical form using a Likert scale to assess the influence of independent, dependent, and intermediary variables. All data were analyzed using Smart-PLS (Partial Least Squares) statistical software. Based on the data processing results, it was found that digitalization positively contributes to employee performance. The higher the intensity of digital technology utilization in work activities, the better the resulting performance. Furthermore, employee engagement has been shown to play a moderating role, strengthening the relationship between digitalization and performance. This means that the positive effect of digitalization on performance will be greater if employees have a strong emotional attachment and commitment to their work.